Effect of soil properties, heavy metals and emerging contaminants in the soil nematodes diversity. (June 2016) - Gutiérrez, Carmen; Fernández, Carlos; Escuer, Miguel; Campos-Herrera, Raquel; Beltrán Rodríguez, Mª Eulalia; Carbonell, Gregoria; Rodríguez Martín, Jose Antonio
Abstract: Among soil organisms, nematodes are seen as the most promising candidates for bioindications of soil health. We hypothesized that the soil nematode community structure would differ in three land use areas (agricultural, forest and industrial soils), be modulated by soil parameters (N, P, K, pH, SOM, CaCO3, granulometric fraction, etc.), and strongly affected by high levels of heavy metals (Cd, Pb, Zn, Cr, Ni, Cu, and Hg) and emerging contaminants (pharmaceuticals and personal care products, PPCPs). Although these pollutants did not significantly affect the total number of free-living nematodes, diversity and structure community indices vastly altered. Our data showed that whereas nematodes with r-strategy were tolerant, genera with k-strategy were negatively affected by the selected pollutants. These effects diminished in soils with high levels of heavy metals given their adaptation to the historical pollution in this area, but not to emerging pollutants like PPCPs. Graphical abstract: Highlights: Free-living nematodes were used to evaluate soil environmental pollution. We provide the first assessment of PPCPs effect on soil free-living nematodes. We found soil pollution evidence due to human activities and mining activities. Heavy metals and emerging contaminants affected the soil nematode community structure. We recorded a genus with k-strategy that was more affected by these pollutants. Abstract : Free-living community soil nematodes revealed adaptation to historical heavy metal pollution, but emergent pollutants are a threat to soil health with an unknown long-term impact.